La filosofía de Virgilio de Córdoba: su tradición filosófica - Lafuente, María Isabel (Agora: Papeles de filosofía, 2017)
An exposition is given of the general topics of Virgilio de Cordoba's work Philosophy that estimate therein the studies categorizing it as a literary work: author's identity, authenticity, structure, philosophy considered as proper of Averroist naturalism. It is shown that a philosophical reading of its nucleus: nigromancy as a science dealing with dubious matters, and the content of its basic philosophical aspects (the first cause, the spirits, and the soul) enables to consider it as proper of the Neoplatonic-Avicennian philosophical tradition propitiating the unity of monotheistic religions, not of the Aristotelic-Averroist tradition.